Humanized Collective Awareness in Islamic Education for Public Prosperity: A Cross-Cultural and Religious Psychological Study - Kana Safrina Rouzi; Fitriah M. Suud; Moh. Toriqul Chaer (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2021)
Islamic education is essential even as the spearhead for the development of religion, culture, and humanity because the aim of Islamic education, in general, is to be rahmatan lil alamin, which means non-discrimination through understanding the meaning of Al-Hujurât: 13. This meaning exists in the offer of teaching solutions with an interfaith and cultural approach with a reflective method. It produces self-awareness that is Islamic education requiring not only teaching religion is essential, but also how to explore and understand more substantive religious values so that one day can become a more spiritual and humanist human being. The purpose of this research is to present text studies as a solution to the current cultural and religious diversity. The result found that collective awareness in the frame of religiosity needs to be in Islamic education for the benefit of the people in a country with a high level of diversity.